Framing French Culture - Edwards, Natalie (University of Adelaide Press, 2015)
Throughout this book, the concept of framing is used to look at art, photography, scientific drawings and cinema as visually constituted, spatially bounded productions. The way these genres relate to that which exists beyond the frame, by means of plastic, chemically transposed, pencil-sketched or moving images allows us to decipher the particular language of the visual and at the same time circumscribe the dialectic between presence and absence that is proper to all visual media. Yet, these kinds of re-framing owe their existence to the ruptures and upheavals that marked the demise of certain discursive systems in the past, announcing the emergence of others that were in turn overturned.